The Impact of the Pandemic on Sports Companies: Comparative Rate Analysis of Champions League and Turkish Football Companies - Ayşe Nur Şahin (Türk Spor ve Egzersiz Dergisi)
Today, when sports have become a very important sector for the economy, football, which is one of the favorite elements of the sports sector, has a very large financial position among other sports branches. Many different organization such as UEFA also contributed to this position. In this study, the effect of the Covid-19 epidemic, which was declared a pandemic by the World Health Organization on March 11, 2020, on football clubs was analyzed through the financial statements of football clubs. In the research, the ratio analysis method was applied through the financial statements of the three football clubs in the category of UEFA champions league leaders as of 5 May 2021 and the football companies traded in the BIST for the periods 2017, 2018, 2019, 2020 and 2021. As a result, it has been revealed that all clubs were affected negatively compared to the pre-pandemic period, but the three clubs, which are UEFA leaders, were less affected by the negatice effects of the pandemic due to their strong financial resources and sporting successes. In the evaluation of the research, it has been revealed that Beşiktaş is the club with the best debt paying power among the clubs in Turkey. It was evaluated that the net working capital of the other three clubs was negative. It is understood that the three clubs, which are the ranking leaders in 2021, have strong financial positions that do not differ much from each other. It is another result that the solvency and resource structures of Turkish football clubs and UEFA ranking leaders are far from each other. This situation is generally; It can be attributed to sportive success, the difference in the income balance and the increase in the exchange rate in our country.